PENGENDALIAN PELAKSANAAN PADA PROYEK JALAN DENGAN EARNED VALUE ANALYSIS - Mei Brilian Harefa; Asri Afriliany Surbakti (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2021)
This study aims to determine the cost and schedule variance (Cost Variance/CV and Schedule Variance/SV), to determine the performance index in terms of cost and time (Cost Performance Index/CPI and Schedule Performance Index/SPI) and to determine the estimated cost and time for project completion. Earned value is one of the methods used to control project implementation. The object of this research is the construction of the Mandeh 1 Tourism Access Road, in Pesisir Selatan Regency, West Sumatra Province. The method used is a descriptive method of analysis carried out by describing with a view to finding the elements, analysis and even comparisons. The data is taken directly from the field so that it is in accordance with the realization in the field. The results showed that the ACWP value was Rp. 37,571,614,926,- , BCWP value of Rp. 41.757.520.198,-, and BCWS of Rp. 41,746,238,807. The CPI value of 1.11 > 1 indicates that the Actuac cost incurred is smaller than the value of the work done or getting a profit. The SPI value of 1 = 1 indicates that the project performance is the same as the planned schedule or there is no work delay. The final cost of completing the EAC project is Rp. 37,679,192,826,18,-. The value of VAC or the difference in the budget between the plan and implementation is Rp. 4,196,794,539.95.